Characterization and Identification Compounds of Liquid Smoke from Used Tire Waste Pyrolysis - Lombok, Johny Zeth; Anom, I Dewa Ketut (Indonesian Journal of Chemical Research, 2023)
Research on compounds from liquid smoke resulting from the pyrolysis of used tire waste has been conducted. The results of tire pyrolysis produce liquid hydrocarbons and charcoal which can be utilized and developed into more useful materials or finished goods. This study aims to identify the compound components of liquid smoke resulting from the pyrolysis of used tire waste. The research begins with manufacturing a pyrolysis tool based on the principle of dry distillation. The pyrolysis process is carried out by heating at high temperatures. Liquid smoke analysis was carried out using GC-MS. In contrast, the components of the compound were identified and characterized by comparing the mass spectrum data obtained with the mass spectrum data in the GC-MS library. The results showed that the pyrolysis of 6 kg of used tires produced 1500 mL of liquid smoke. Analysis of liquid smoke by GC-MS produced 88 chromatogram peaks, with the most dominant peak height at peaks 3, 17, 37, 38, 72, and 73. The most dominant compound component identified by MS spectrum analysis is 2-propanone (peak 3), 4-methyl-2-pentanone (peak 17), ethyl-benzene (peak 37), 1,2-dimethyl-benzene (peak 38), 1-methyl-4-(1-methyl ethyl)-benzene (peak 72) and limonene (peak 73).